Digital Accounting Innovation for SMEs: The Role of Smita Akuntansi in Supporting Financial Management for Gen Z Entrepreneurs - Sudyantara, Smita Catur; Hilma , Oktavian Miftahul (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia’s economic growth; however, many still face challenges in financial management due to limited accounting literacy and a tendency to mix personal and business finances. Digital accounting innovation offers an opportunity to improve financial recording and reporting practices, especially among Gen Z entrepreneurs who are more adaptive to technology. This study examines the influence of perceived usefulness and perceived ease of use on the behavioral intention to use the Smita Akuntansi Mikro application, based on the Technology Acceptance Model (TAM). Using a quantitative approach with 50 Gen Z MSME respondents, data were collected through a survey and analyzed using linear regression. The results show that both perceived usefulness and ease of use have a positive and significant effect on the intention to use Smita Akuntansi Mikro, with the model explaining 76% of the variation in usage intention. These findings indicate that simple interface design and clear financial benefits increase users’ willingness to adopt digital accounting tools. Thus, Smita Akuntansi Mikro has strong potential to improve financial literacy, discipline, and business sustainability among young MSME entrepreneurs